(untitled) (Journal of actual problems of jurisprudence, 2018)
The article deals with the problems of legal regulation in the sphere of tax administration of the Republic of Kazakhstan. In conditions of severe economic crisis, not only in Kazakhstan but also in the literal sense as if the pace of growing global economic recession in the world economic downturn is naturally called for a specific negative phenomena. Occurred in the country’s currency devaluation showed that all of the world economy, are closely interlinked. Key words: legal regulation, tax administration, National currency.